Investigating the Role of Aesthetics in Consumer Moral Judgment and Creativity - (:unkn) unknown (My University, 2016)
ABSTRACT As human beings, we have a profound affinity for beauty, and an overwhelming amount of research recognizes our attraction to high aesthetics. Aesthetics significantly affect consumer behavior, such as purchase intention, product perception, consumer satisfaction, and product evaluation. Leading brands such as Apple are adored and coveted due to the high aesthetics and superior design of their products, which enables them to create and sustain competitive advantage. Because consumers often give more importance to aesthetics than functional attributes when choosing a product, marketers take aesthetics into account in their marketing strategies. This research explores aesthetics’ diverse relationships to consumer behavior. Specifically, I examine the relationship of aesthetics to consumers’ moral judgment and creativity and consider the moderating roles of individual traits, such as the centrality of aesthetics in one’s life and construal level. In essay I, I start by summarizing the general literature on aesthetics and the literature that is specific to marketing and consumer behavior. In essay II, I explore the effects of beauty on consumers’ moral judgment. Consumers often have to choose between what is right and what is easy, such as in paying more for fair-trade coffee, purchasing low-carbon footprint products, or recycling. Typically, consumers sacrifice money, time, or effort to make moral choices, and several factors are salient to these decision-making processes. The findings of the initial studies indicate that beauty does affect moral judgment. Additionally, verbal and visual beauty cues have distinct effects on moral judgment. Visual beauty cues overpower moral judgment, making consumers are less willing to forgo beauty to make morally responsible choices. On the other hand, verbal beauty cues induce consumers to make morally sound decisions when visual cues are not present. There is a dearth of research on the effects of product aesthetics on consumers’ moral judgment, and I seek to fill this gap. In essay III, I focus on the relationship between nature scenes and creativity while accounting for the centrality of visual product aesthetics. Additionally, I explore the moderating role of construal level. I posit that consumers who assign higher importance to product aesthetics are more likely to be creative when exposed to nature scenes. Research indicates that spending time in nature has soothing and restorative properties, such as stress relief, lower depression, and overall wellbeing. Moreover, research shows that a soothing natural environment facilitates the mental wellbeing that is conducive to creativity. The results indicate an interaction between scenery and creativity and that this relationship is moderated by the centrality of aesthetics in one’s life. Specifically, I observe improved creativity on exposure to nature scenes, and this relationship is significant for individuals who give higher importance to product aesthetics, finding that the centrality of aesthetics in one’s life extends to the appreciation of beauty in nature, as anticipated, and enhances creativity. The results also indicate a significant interaction between scenery and construal level; as anticipated, individuals with a low/concrete construal demonstrate a higher propensity toward creativity on exposure to nature scenes when compared to individuals with a high/abstract construal. This research provides a fresh perspective on the salience of aesthetics and contributes to the scarcity of research into moral judgment and creativity in consumer behavior.